Disappearing microbiota and human metabolic health - Blaser, Martin (Henry Stewart Talks, 2011)
The microbiome is ancient and performs important physiologic functions in humans, The microbiome has been changing in recent years with consequences for both health and disease, The changing ecology of the stomach with relation to Helicobacter pylori provides one example of changed physiology, and disease risk, Animal models with early life exposure to antibiotics provide a second example of altered metabolism